Physical structure of leather tanned with aluminium as an alternative tanning agent - Anggriyani, Emiliana; Adetya, Nais Pinta; Rachmawati, Laili; Nurwantoro, Nurwantoro (Universitas Sebelas Maret, 2023)
Objective: This study aims to examine the physical structure of goat skins tanned with aluminium as an alternative tanning agent.Methods: Twelve pieces of goat skin from the pikle breed were used in the study. Chromosal B, an aluminium tanning agent, Novaltan Al, salt (NaCl), Derminol OCS, MgO, Sodium bicarbonate, a BCG indicator, Permit MLN, and an anti-fungal are among the chemicals utilized. The approach involves tanning using chrome tanning as a control and aluminum tanning with amounts of 2%, 4%, and 6% Al2O3. Cross-sectional tests were used to assess the wet white leather's results, and the SEM-EDX method was used to determine the leather's composition.Results: Leather tanned with aluminium tanning agent shows the distribution of aluminium in the skin section, the increasing use of aluminium tanning materials, the higher the aluminium content in tanned leather.Conclusions: The presence of aluminium tanning agent in the skin indicates an interaction between the material and the skin so that it can be used as an alternative tanning agent.